Pengaruh Penambahan Hidroksi Apatit Dari Serbuk Cangkang Telur Terhadap Kekuatan Tarik Diametral Semen Ionomer Kaca Modifikasi Resin (SIKMR) - Lusianita, Fera, drg. Noor Hafida Widyastuti, Sp.KG (2017)
Semen ionomer kaca modifikasi resin (SIKMR) or resin-modified glass ionomer cement (RM-GIC) are restorative material produced from the merger of the conventional glass ionomer cements with composite resin, but its use was limited because RMGIC have a low tensile strength. Various efforts undertaken to improve the diametral tensile strength of RMGIC, one of them by mixing hydroxyapatite powder from eggshell into RMGIC powder. Hydroxyapatite can be synthesized by using the method of precipitation by mixing calcium's precursor and phosphate's precursor. The purpose of this study is to notice at the effect of adding hydroxy apatite from eggshell powder to the material diametral tensile strength of resin modified glass ionomer cements. This study used 32 samples with 6 mm of diameter and 3 mm height and divided into 2 groups: first group were SIKMR without hydroxyapatite as a control group with 16 samples and the second group were SIKMR with the addition of 8% hydroxyapatite as test groups totaling 16 samples. The diametral tensile strength calculated using a universal testing machine (UTM) with speed of 0.5 mm / min. The data collected were analyzed by Independent t-test on 95% significance level. The measurement results average diametral tensile strength of the control group was 38.6363 ±, 97 188 MPa and the test group was 43.1606 ± 1.38930. Results of independent t-test showed that between the two study groups there are significantly value differences in diametral tensile strength (Sig <0.05). it can be concluded that addition of hydroxy apatite effected to improve diametral tensile strength of Resin modified glass ionomer.